The Search for a Cultural Crossroad in a Diverse City: The MuCem in Marseille - Dias, N. (Museums and their Publics at Sites of Conflicted History, 2017)
Three aspects will be explored in this presentation. First, I begin by examining the museum’s goal, that is to be a new type of museum in resonance with current geopolitical concerns. The MuCem aims to be a cultural center, a forum, a pluridisciplinary institution, a museum of a type never seen before. To what extent does the MuCem break the links with the former museological models and can be considered as a new kind of cultural institution? The second aspect, and closely related with the previous one, deals with the ways in which the MuCem aims to participate in ‘making citizens’, and how the notion of citizenship along with the notion of diversity are at the core of this institution in general and of the third section of the MuCem’s permanent exhibition entitled ‘Citizenship and human rights’. The third and last aspect concerns the role assigned to France’s colonial memories within this institution, which aims to overcome the ‘memory wars’ and to establish a new kind of bonds between peoples living in the two shores of the Mediterranean.